Modified Soda Lignin for Improvement of Interfacial Adhesion in Wood-Plastic Composites - Galia Shulga; Brigita Neiberte; Jevgenijs Jaunslavietis; Anrijs Verovkins; Sanita Vitolina; Vadims Shakels; Sandra Liveha (Chemical and Materials Sciences: Research Findings Vol. 1, 2025)
The principles of the Circular Economy dictate the sustainable, rational, and efficient management of wastes and by-products because their annual volume remarkably increases and negatively affects the environment. Here, a lignin-containing adhesion enhancer, a water-soluble polyelectrolyte complex (LPEC) composed of soda hardwood lignin (HASL) and polyethyleneimine (PEI), and the effect of the treatment of hydrolyzed and ammoxidized aspen sawdust with the LPEC nanoparticles were studied relative to the properties of wood-plastic composites (WPCs) based on recycled polypropylene (rPP). Here, aspen sawdust, representative of a waste of the mechanical processing of aspen wood (Populus tremula), was supplied by a Latvian company (4 PLUS Ltd., Aizkraukle, Latvia). The presence of the excess of free amine groups and salt bonds between PEI and soda lignin, forming hydrophobic sites in the LPEC structure, caused the enhanced surface activity of the LPEC. The treatment with the LPEC nanoparticles increased the content of the fixed nitrogen in the modified sawdust samples and was accompanied by decreasing their water sorption and increasing contact angles that favored the decrease in the polar part of their surface free energy. The decreasing wetting ability enhanced the mechanical and water sorption properties of the obtained WPC samples. The improvement of the interfacial adhesion between the nitrogen-containing groups of the treated sawdust and the oxygen-containing groups of rPP was explained by the formation of both covalent and physicochemical bonds.